Medicago truncatula Zinc-Iron Permease6 provides zinc to rhizobia-infected nodule cells - Abreu, Isidro; Saéz, Ángela; Escudero, Viviana; Senovilla, Marta; Larue, Camille; Grolimund, Daniel; Imperial, Juan; Castro Rodríguez, Rosario; Rodríguez Haas, Benjamín; González Guerrero, Manuel; Tejada Jiménez, Manuel (My University, 2024)
Zinc is a micronutrient required for symbiotic nitrogen fixation. It has been proposed that in model legume Medicago truncatula, zinc is delivered by the root vasculature into the nodule and released in the infection/differentiation zone. There, transporters must introduce this element into rhizobia¿infected cells to metallate the apoproteins that use zinc as a cofactor. MtZIP6 (Medtr4g083570) is an M. truncatula Zinc¿Iron Permease (ZIP) that is expressed only in roots and nodules, with the highest expression levels in the infection/differentiation zone. Immunolocalization studies indicate that it is located in the plasma membrane of nodule rhizobia¿infected cells. Down¿regulating MtZIP6 expression levels with RNAi does not result in any strong phenotype when plants are fed mineral nitrogen. However, these plants displayed severe growth defects when they depended on nitrogen fixed by their nodules, losing of 80% of their nitrogenase activity. The reduction of this activity was likely an indirect effect of zinc being retained in the infection/differentiation zone and not reaching the cytosol of rhizobia¿ infected cells. These data are consistent with a model in which MtZIP6 would be responsible for zinc uptake by rhizobia¿infected nodule cells in the infection/differentiation zone. KEYWORDS nodule, symbiotic nitrogen fixation, Zinc¿Iron Permease